2020
DOI: 10.1002/fsn3.2090
|View full text |Cite
|
Sign up to set email alerts
|

The hepatoprotective effects of fennel seeds extract and trans‐Anethole in streptozotocin‐induced liver injury in rats

Abstract: Hypoglycemic, anti‐inflammatory, and antioxidant activities of fennel have been recorded in numerous investigations. The study aimed to evaluate the protective effects of fennel or its active component trans‐Anethole (TA) on streptozotocin‐induced liver injury in rats. Rats were injected with a single dose of STZ (65 mg/kg) and treated with fennel (200 and 400 mg/kg), TA (80 mg/kg), or metformin (300 mg/kg) for 35 days. Serum lipid profile and liver enzyme activity (aminotransferases), oxidative stress markers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 62 publications
2
34
0
Order By: Relevance
“…Interestingly, the fennel plant (Foeniculum vulgare) is a flowering plant species which showed potent activity against a wide range of disorders, including reproduction [13], respiratory [14], gastrointestinal [15] and endocrinal problems [16], besides its role as a lactation-improving agent [17]. Furthermore, fennel has shown potent antioxidant, antibacterial, antifungal, anti-inflammatory, and antiparasitic activities [18,19]. Fennel seed can also be used as a natural flavoring for some foods such as bread, cheese and pickles.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the fennel plant (Foeniculum vulgare) is a flowering plant species which showed potent activity against a wide range of disorders, including reproduction [13], respiratory [14], gastrointestinal [15] and endocrinal problems [16], besides its role as a lactation-improving agent [17]. Furthermore, fennel has shown potent antioxidant, antibacterial, antifungal, anti-inflammatory, and antiparasitic activities [18,19]. Fennel seed can also be used as a natural flavoring for some foods such as bread, cheese and pickles.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes is the leading cause of hepatic disorders in the USA. Many studies have shown that liver disease is an important cause of morbidity and mortality in type-II diabetes (T2DM) [ 3 ]. Besides the high prevalence of liver disease in diabetic patients, the incidence of diabetes is higher in patients with liver disease.…”
Section: Introductionmentioning
confidence: 99%
“…Now the compound anethole being reported several times that it possess hepatoprotective effects which makes the compound a perfect candidate for down regulation of diabetic conditions. One of such study on streptozotocin induced liver injury in rats was reported to protect the liver against diabetic induced hepatic injury upon trans- anethole treatment 40 . According to the report, the mechanism behind being trans- anethole as hepatoprotective agent is due to its hypoglycemic and antioxidative effects.…”
Section: Discussionmentioning
confidence: 99%